The Basics of Food Traceability - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
This publication explains the concept of traceability systems in the food industry and discusses its main components. It includes a list of key traceability requirements established internationally and in European legislation. It also uses the case of Ukraine to illustrate implementation of food traceability on the national level.